Characterizing Subsiding Shells in Shallow Cumulus Using Doppler Lidar and Large‐Eddy Simulation. Issue 18 (14th September 2020) - McMichael, Lucas A.; Yang, Fan; Marke, Tobias; Löhnert, Ulrich; Mechem, David B.; Vogelmann, Andrew M.; Sanchez, Kevin; Tuononen, Minttu; Schween, Jan H.
Abstract: The existence of subsiding shells on the periphery of shallow cumulus clouds has major implications concerning the parameterization of shallow convection, with the mass exchange between the shell and cloudy air representing a significant deviation from the commonly used bulk‐plume parameterization. We examine the structure and frequency of subsiding shells in shallow cumulus convection using Doppler lidars at the Atmospheric Radiation Measurement Southern Great Plains facility in the central United States and at the Jülich ObservatorY for Cloud Evolution in western Germany. Doppler lidar indicates that the vertical subsiding shell extent is asymmetric, while shell width is typically 100 m. Large‐eddy simulation can reasonably simulate the observed shell structure using a grid spacing of 10 m and suggests that much of the observed asymmetry is not a result of transient cloud evolution. Plain Language Summary: Doppler lidars allow for the inference of vertical air motion. On the edges of the shallow "popcorn" cumulus clouds, regions of sinking air (subsiding shells) are observed. If we wish to understand how these clouds interact with their environment, we must understand the structure of the subsiding shells that envelop them. As a cloud passes over the lidar, the front edge of the cloud is sampled first, and the back edge is sampled later. The back‐edge subsiding shell descends farther below cloud base than the front‐edge shell. High‐resolution models can resolve the observed shell structure and suggest that the differences between the front‐ and back‐edge shells do not arise from the evolution of the cloud during the tens of seconds it takes to pass over the lidar. Key Points: Doppler lidar indicates the presence of a vertically asymmetric subsiding shell in shallow cumulus that is on the order of 100 m wide Large‐eddy simulations can reasonably reproduce observed shell structure and intensity Most of the asymmetry observed by lidar reflects fundamental cloud structures and is not simply a consequence of the sampling method